Consensus-Based Distributed Control for Improving the Sharing of Unbalanced Currents in Three-phase Three-wire Isolated Microgrids - Burgos-Mellado, Claudio; Donoso, Felipe; Llanos, Jacqueline; Martinez-Gomez, Manuel; Morales-Paredes, Helmo K. [UNESP]; Torres, Miguel (Institute of Electrical and Electronics Engineers (IEEE), 2021)
This paper proposes a secondary distributed control strategy to achieve the sharing of unbalanced currents between 3-leg power converters, operating under droop control, in a three-phase three-wire isolated Microgrid (MG). To this end, a modified Q-E droop controller is used, where new control actions are defined to achieve the unbalanced currents sharing amongst the converters. These control actions are generated, in the secondary control level, by a consensus-based algorithm, where the consensus variables correspond to the single-phase reactive powers of the converters. This paper shows that sharing negative sequence current components amongst the power converters can be managed by achieving a consensus (per phase) of single-phase reactive powers. Extensive simulations demonstrate the excellent performance of the proposed controller.
Keywords: Consensus protocol; Distributed control; Imbalance Sharing; Isolated Microgrid; Single-Phase Reactive Power